Hypoxia in Drosophila Embryonic Development: Implications for Organ Preservation - Dong, Kelly (The Meducator, 2016)
In organ preservation, the prevalent problem has always been time: time to analyze the organ, match the organ to a recipient, store the organ, transport the organ, and transplant the organ. Due to the quick rate at which tissue deteriorates outside the body, whether that be a result of loss of blood flow or cellular damage from the hypothermic method` of storage. The experiment investigates the effect that low oxygen (hypoxia) and low temperature has on the development of embryos as an alternative that may be less detrimental. As demonstrated on the test subject Drosophila melanogaster (fruit flies), both factors can induce a state of suspended animation, which is a condition in which the test subject stops aging during development. Hypoxia can successfully arrest development for up to three times the regular development time, which is around 22 hours at 25°C. At lower temperatures, a greater number of oxygen concentrations are viable and are able to induce suspended animation for a greater period of time. The results of the experiment may suggest that hypoxia is a possible alternative that may extend the time and reduce tissue damage for organ preservation.